Esthesioneuroblastoma: clinical course, long-term results of treatment - T. D. Tabolinovskaya; A. M. Mudunov; S. B. Alieva; N. F. Orel; L. E. Komarova; E. R. Oganyan; I. N. Pustynskiy; R. A. Khasanov; T. A. Aketova; N. A. Pirogova (Опухоли головы и шеи, 2016)
This rare tumor from a group of neuroendocrine neoplasms was studied. The material for the study was the data of 78 patients with esthesioneuroblastoma who had been treated and followed up at the N.N. Blokhin Russian Cancer Research Center in the period 1965 to 2014. Information on hospital statistics, clinical features, methods, and treatment results were presented. The possibilities of using the TNM classification for the nasal cavity, ethmoidal sinuses, and nasopharynx were assessed to determine the anatomic extent of primary tumor. The findings contribute to the solution of problems in the diagnosis and treatment of esthesioneuroblastoma at the present stage.